Preparation method of in-situ graphene-copper / nickel composite material based on solid / liquid phase change
By using the directional solidification process and solid/liquid phase transformation process in a high-pressure furnace, the in-situ deposition and uniform distribution of graphene on the copper matrix is achieved, which solves the problem that graphene is difficult to disperse uniformly on the copper matrix and easily damaged structure, and significantly improves the comprehensive performance of the composite material.
Patent Information
- Application Number
- CN202510017663.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-06
AI Technical Summary
In the preparation of existing graphene-reinforced copper-based composite materials, graphene is difficult to disperse uniformly on the copper matrix and easily agglomerate, resulting in a decline in the comprehensive performance of the composite material. At the same time, the structure of graphene is easily damaged, resulting in lattice defects, and affecting the enhancement effect; the poor wettability between copper and graphene also affects the interface binding ability.
The directional solidification process is used to pass H2 and CH4 gas into the high-pressure furnace, and supersaturated hydrogen and carbon atoms are used to precipitate during the solid/liquid phase transition to form hydrogen bubbles and graphene films, and a three-dimensional graphene network structure is formed through directional movement to achieve in-situ deposition.
The uniform distribution and high-quality growth of graphene are achieved, which significantly improves the strength, toughness, fatigue resistance and conductivity of the composite material, enhances the interface bonding strength, and reduces processing difficulty and production costs.
Smart Images

Figure CN119824271A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of material science and engineering technology, and in particular to a method for preparing an in-situ graphene-copper / nickel composite material based on solid / liquid phase transition. Background Art
[0002] Graphene has excellent mechanical and physical properties. Its fracture strength and Young's modulus are as high as 130 and 1100 GPa, and its carrier mobility is 15000 cm 2 ·V -1 ·S -1 , thermal conductivity is 5000W·m -1 ·K -1 , which is three times that of pure diamond at room temperature. With the deepening of research, three-dimensional graphene (3DGNs) composed of two-dimensional graphene sheets have gradually shown better comprehensive properties and have attracted widespread attention.
[0003] Copper-based graphene composite material is a new type of composite material composed of copper and graphene. The introduction of graphene into the copper matrix can not only improve the oxidation resistance of copper, protect the copper surface from corrosion, and extend the service life, but also maintain good electrical and thermal conductivity while improving mechanical properties. It expands the application field of copper materials in extreme environments such as high temperature and high pressure.
[0004] At present, the preparation of graphene-reinforced copper-based composites often faces the problem that graphene is difficult to disperse evenly on the copper matrix and is prone to agglomeration, which leads to reduced comprehensive performance of the composite material. During the preparation process, the structure of graphene is easily destroyed, resulting in lattice defects, which reduces the reinforcement effect of graphene. Due to the poor wettability between copper and graphene, the problem of graphene-copper interface bonding ability has also become one of the factors affecting the performance of composite materials.
[0005] Gasar is a method for preparing porous metals. Due to the poor solubility of gas in the liquid and solid phases of metals, the supersaturated gas at the solidification interface will precipitate to form bubbles, which will further grow along the solidification direction, and finally obtain a porous material with cylindrical pores. Chemical vapor deposition uses different carbon sources as precursors and transition metals as substrates. The carbon sources are cracked into carbon atoms under high temperature and catalysis, and then rearranged on the substrate to form a graphene film.
[0006] The existing Chinese patent document CN117604491 A discloses a three-dimensional graphene-reinforced copper-based composite material, a preparation method and an application thereof. Graphene is in situ deposited on the surface of copper foam by chemical vapor deposition to construct a three-dimensional graphene network structure. However, during the deposition process, due to the complex structure of copper foam, the graphene is distributed unevenly on the surface, which easily leads to graphene agglomeration, thereby affecting the overall performance of the composite material. At the same time, the multiple steps in the preparation method are relatively complicated, and the equipment and operating conditions are strictly required, which easily leads to batch differences and poor repeatability.
[0007] In view of the above problems, the present invention proposes a preparation method combining Gasar porous metal preparation technology with graphene in-situ deposition technology. With the help of traditional directional solidification process, the preparation of porous metal substrate and the in-situ deposition of three-dimensional graphene during solid / liquid phase change are realized in the same reactor, and finally a three-dimensional graphene-reinforced porous composite material with excellent performance is prepared, which improves the performance consistency and stability of the composite material. Summary of the invention
[0008] The purpose of the present invention is to provide a method for preparing an in-situ graphene-copper / nickel composite material based on solid / liquid phase transition, so as to realize the preparation of porous metal and in-situ deposition of three-dimensional graphene in the same reactor, and finally obtain a three-dimensional graphene-reinforced porous composite material with excellent comprehensive performance.
[0009] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:
[0010] With the help of directional solidification process, H2, a working gas related to the preparation of porous substrates, and CH4, a carbon source required for graphene deposition, are introduced into a high-pressure melting furnace at the same time. The two gases decompose and dissolve into the metal melt respectively. When the temperature of the metal melt drops, the melt undergoes a solid / liquid phase transition, and the supersaturated hydrogen and carbon atoms dissolved in it precipitate one after another. Hydrogen atoms continue to gather to form hydrogen bubbles, and supersaturated carbon atoms continue to precipitate in a hydrogen atmosphere and are connected into clusters through carbon-carbon bonds, eventually forming a graphene film. Thereafter, the hydrogen bubbles and the graphene film move in a directional manner along the solid-liquid interface, and a graphene-enhanced porous composite material is formed after the substrate is cooled.
[0011] A method for preparing an in-situ graphene-copper / nickel composite material based on solid / liquid phase transition comprises the following steps:
[0012] S1: Prepare the metal melt: put the weighed metal into the crucible and lock the reaction furnace. Evacuate the furnace to 10 - 2 Pa, turn on the heating power, control the temperature to the set temperature and keep it warm;
[0013] S2: After the completion of S1, H2 and CH4 are introduced into the reactor to a given pressure and kept warm for a period of time;
[0014] S3: After S2 is completed, pour the molten metal in the crucible into a graphite mold for directional solidification, and control the solidification rate during the solidification process;
[0015] S4: After the completion of S3, when the temperature in the furnace drops to room temperature, open the vent valve, release the gas in the furnace, open the furnace cover, and take out the sample.
[0016] Furthermore, the metals in S1 are respectively high-purity copper (99.99%), high-purity nickel (99.99%) and copper-nickel alloy (nickel content is 50%-80wt%, copper content is 20%-50wt%). When smelting high-purity copper, the set temperature is 1560K and the holding time is 5min. When smelting high-purity nickel, the set temperature is 2000K and the holding time is 5min. When smelting high-purity copper-nickel alloy, the set temperature is 2000K and the holding time is 10min.
[0017] Furthermore, in S2, the gases introduced into the reactor are all high-purity gases. Among them, the pressure range of H2 is 1.5-2.5MPa; the pressure range of CH4 is 1.5-2.5MPa. The insulation time is set to 15min, so that the two gases can fully diffuse into the metal melt;
[0018] Furthermore, in S3, the cooling and solidification rate is 20-150K / min when smelting high-purity copper, and the cooling and solidification rate is 20-100K / min when smelting high-purity copper-nickel alloy;
[0019] Beneficial effects of the present invention:
[0020] The present invention adopts a directional solidification process to prepare a graphene-enhanced composite material. The metal melt is in a mixed atmosphere of H2 and CH4. When a solid-liquid phase change occurs, supersaturated hydrogen atoms and carbon atoms precipitate and grow together to form hydrogen bubbles and graphene films. The two move directional along the solid-liquid interface, and finally form a three-dimensional graphene-enhanced porous composite material. The carbon atoms produced by the decomposition of CH4 nucleate and grow on the surface and inner wall of the porous metal matrix at high temperature to form a three-dimensional interconnected graphene network structure. The H2 atmosphere plays a protective role, preventing metal oxidation and providing a reducing environment, which is conducive to the high-quality growth of graphene. The uniformly distributed three-dimensional graphene network not only significantly improves the strength, toughness and fatigue resistance of the composite material, but also forms a continuous conductive path, greatly improving its conductivity. This is in sharp contrast to the traditional method, where graphene is easy to agglomerate and has poor dispersibility, resulting in limited improvement in mechanical properties and discontinuous conductive paths. In-situ growth ensures that graphene is closely combined with the matrix, maximizes the strengthening effect of graphene, and avoids the strength drop caused by interface debonding. The use of copper-nickel alloy as the matrix material further improves the strength, hardness and corrosion resistance of the composite material. The advantage of nickel metal being stronger in dissolving carbon than copper metal is effectively utilized, ensuring sufficient carbon source supply for the subsequent deposition and growth of graphene.
[0021] The biggest advantage of the present invention is that the preparation of porous metal matrix and the in-situ growth of graphene are integrated into the same reactor, realizing the integration of the process. The traditional preparation method usually needs to prepare a porous copper matrix first, then introduce graphene by physical methods (such as mixing, coating), and finally need to carry out complex steps such as high temperature sintering. These steps are not only time-consuming, but also easy to introduce defects, reducing product quality. The integrated preparation process of the present invention significantly reduces the process steps and intermediate links, reduces production costs and energy consumption, shortens the production cycle, and improves production efficiency. In addition, the complex graphene dispersion and mixing steps are omitted, avoiding the structural damage and performance loss of graphene during the treatment process, and ensuring the high quality of graphene. The H2 required for the preparation of porous metal and the carbon source CH4 required for graphene deposition are introduced simultaneously, and the difference in the solubility of hydrogen atoms and carbon atoms in different metal phases is utilized. Hydrogen atoms and carbon atoms are precipitated respectively during the solid-liquid phase transition to form hydrogen bubbles and graphene films. During the directional solidification process, the two continued to grow in the same direction along the solid-liquid interface, ultimately achieving the preparation of porous metal and the in-situ deposition of three-dimensional graphene on the pore wall surface, greatly simplifying the preparation process of three-dimensional graphene-reinforced porous copper / nickel composites and reducing processing difficulty.
[0022] The present invention realizes the close combination of graphene and matrix on the atomic scale by the method of in-situ growth. This is in sharp contrast to the interface defects and weak bonding between graphene and matrix in the traditional method. Strong chemical bonding is formed between the graphene grown in situ and the matrix during the solid-liquid phase transition, which significantly improves the interface bonding strength, effectively prevents interface debonding and crack propagation, thereby improving the overall mechanical properties and fatigue resistance of the composite material, and enhancing the oxidation resistance and corrosion resistance of the material. The in-situ deposition of graphene on porous copper / nickel (copper-nickel alloy) wall not only solves the problem of unstable bonding interface caused by poor wettability between graphene and copper matrix, but also the graphene thin layer is evenly dispersed and the growth quality is high. In addition, the porous copper (copper-nickel alloy) wall can guide the graphene deposition into a three-dimensional structure (3DGNs), improve the interface shear strength, and play an important role in improving the comprehensive performance of the composite material.
[0023] The present invention achieves the microstructure and performance of the final composite material by precisely controlling the reaction atmosphere (the partial pressure ratio of H2 and CH4), the holding time, and the directional solidification rate. By adjusting the gas pressure and ratio, the thickness, density, and distribution of graphene can be controlled; by controlling the solidification rate, the size and distribution of the porous structure can be regulated, which ultimately affects the mechanical properties and electrical conductivity of the composite material. For different matrix materials (high-purity copper / nickel and copper-nickel alloy), the present invention optimizes the process parameters respectively to ensure that composite materials with excellent performance can be obtained on different matrix materials. This ability to precisely control the microstructure and performance provides strong technical support for the research and development of composite materials with specific performance requirements, and expands its application potential in various fields.
[0024] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0026] Figure 1 (a) Macroscopic image of the longitudinal section of porous copper, (b) Macroscopic image of the longitudinal section of porous copper-nickel alloy, (c) morphology of graphene-copper / nickel composite material. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] The method for preparing an in-situ graphene-copper / nickel composite material based on solid / liquid phase transition described in this embodiment comprises the following steps:
[0030] S1: preparing pure copper melt;
[0031] S2: introducing working gas H2 and carbon source CH4 to a given pressure and keeping warm;
[0032] S3: pure copper melt is poured into the graphite mold for directional solidification to control the solidification rate;
[0033] S4: Take out the sample after the reaction furnace cools down to room temperature.
[0034] In the step S1 of preparing pure copper melt, high-purity copper (99.99%) is used for smelting, and the furnace is evacuated to 10 -2 Pa, the melting temperature was set to 1560K and the holding time was 5min;
[0035] In step S2, the pressures of the working gas H2 and the carbon source CH4 are 1.5 MPa and 2.5 MPa respectively, and the insulation time is 15 min;
[0036] The cooling rate during the directional solidification in step S3 is 60K / min.
[0037] After the experiment, the samples were taken out and the pore size distribution and porosity of the samples were statistically analyzed. The internal structure of graphene was tested using Raman spectroscopy. The tensile strength was tested along the direction parallel to the pore size.
[0038] Example 2
[0039] The method for preparing an in-situ graphene-copper / nickel composite material based on solid / liquid phase transition described in this embodiment comprises the following steps:
[0040] S1: preparing pure copper melt;
[0041] S2: introducing working gas H2 and carbon source CH4 to a given pressure and keeping warm;
[0042] S3: pure copper melt is poured into the graphite mold for directional solidification to control the solidification rate;
[0043] S4: Take out the sample after the reaction furnace cools down to room temperature.
[0044] In the step S1 of preparing pure copper melt, high-purity copper (99.99%) is used for smelting, and the furnace is evacuated to 10 -2 Pa, the melting temperature was set to 1560K and the holding time was 5min;
[0045] In step S2, the pressures of the working gas H2 and the carbon source CH4 are 1 MPa and 3 MPa respectively, and the insulation time is 15 min;
[0046] The cooling rate during the directional solidification in step S3 is 60K / min.
[0047] After the experiment, the samples were taken out and the pore size distribution and porosity of the samples were statistically analyzed. The internal structure of graphene was tested using Raman spectroscopy. The tensile strength was tested along the direction parallel to the pore size.
[0048] Example 3
[0049] The method for preparing an in-situ graphene-copper / nickel composite material based on solid / liquid phase transition described in this embodiment comprises the following steps:
[0050] S1: preparing pure nickel melt;
[0051] S2: introducing working gas H2 and carbon source CH4 to a given pressure and keeping warm;
[0052] S3: pure copper melt is poured into the graphite mold for directional solidification to control the solidification rate;
[0053] S4: Take out the sample after the reaction furnace cools down to room temperature.
[0054] In the step S1, high-purity nickel (99.99%) is used for smelting, and the furnace is evacuated to 10 -2 Pa, set the melting temperature to 2000K and the holding time to 5min;
[0055] In step S2, the pressures of the working gas H2 and the carbon source CH4 are 1.5 MPa and 2.5 MPa respectively, and the insulation time is 15 min;
[0056] The cooling rate during the directional solidification in step S3 is 60K / min.
[0057] After the experiment, the samples were taken out and the pore size distribution and porosity of the samples were statistically analyzed. The internal structure of graphene was tested using Raman spectroscopy. The tensile strength was tested along the direction parallel to the pore size.
[0058] Example 4
[0059] The method for preparing an in-situ graphene-copper / nickel composite material based on solid / liquid phase transition described in this embodiment comprises the following steps:
[0060] S1: preparing a copper-nickel alloy melt;
[0061] S2: introducing working gas H2 and carbon source CH4 to a given pressure and keeping warm;
[0062] S3: pure copper melt is poured into the graphite mold for directional solidification to control the solidification rate;
[0063] S4: Take out the sample after the reaction furnace cools down to room temperature.
[0064] In the step S1, high-purity copper (99.99%) and high-purity nickel (99.99%) are used for smelting. The nickel content is 60wt%, the copper content is 40wt%, and the furnace is evacuated to 10 before heating. -2 Pa, set the melting temperature to 2000K and the holding time to 10min;
[0065] In step S2, the pressures of the working gas H2 and the carbon source CH4 are 2MPa and 2MPa respectively, and the insulation time is 15min;
[0066] The cooling rate during the directional solidification in step S3 is 40K / min.
[0067] After the experiment, the samples were taken out and the pore size distribution and porosity of the samples were statistically analyzed. The internal structure of graphene was tested using Raman spectroscopy. The tensile strength was tested along the direction parallel to the pore size.
[0068] Table 1 Product performance statistics in Examples 1-4
[0069]
[0070] In summary, the present invention proposes a method for preparing an in-situ graphene-copper / nickel composite material based on solid / liquid phase transition. By in-situ growing three-dimensional graphene during directional solidification, the problems of poor graphene dispersion, weak interface bonding, and complex preparation process in traditional methods are effectively solved, and finally a three-dimensional graphene-reinforced porous copper-based composite material with excellent comprehensive performance is obtained.
[0071] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing an in-situ graphene-copper / nickel composite material based on solid / liquid phase transition, characterized in that: The following steps are involved: S1: Put the weighed metal into the crucible and lock the reaction furnace; evacuate the furnace to 10 -2 Pa, turn on the heating power, control the temperature to the set temperature and keep it warm; S2: introduce H2 and CH4 into the reactor to a given pressure and keep it warm for a period of time; S3: pouring the molten metal in the crucible into a graphite mold for directional solidification, and controlling the solidification rate during the solidification process; S4: When the temperature in the furnace drops to room temperature, open the vent valve to release the gas in the furnace and obtain the sample.
2. The method for preparing an in-situ graphene-copper / nickel composite material based on solid / liquid phase transition according to claim 1, characterized in that: The metals in S1 are high-purity copper, high-purity nickel and copper-nickel alloy respectively. When smelting high-purity copper, the set temperature is 1560K and the insulation time is 5 minutes; when smelting high-purity nickel, the set temperature is 2000K and the insulation time is 5 minutes; when smelting high-purity copper-nickel alloy, the set temperature is 2000K and the insulation time is 10 minutes.
3. The method for preparing an in-situ graphene-copper / nickel composite material based on solid / liquid phase transition according to claim 1, characterized in that: The copper-nickel alloy has a nickel content of 50%-80wt% and a copper content of 20%-50wt%.
4. The method for preparing an in-situ graphene-copper / nickel composite material based on solid / liquid phase transition according to claim 1, characterized in that: In S2, the gases introduced into the reaction furnace are all high-purity gases; among them, the pressure range of H2 is 1.5-2.5MPa; the pressure range of CH4 is 1.5-2.5MPa; the insulation time is set to 15min, so that the two gases can fully diffuse into the metal melt.
5. The method for preparing an in-situ graphene-copper / nickel composite material based on solid / liquid phase transition according to claim 1, characterized in that: In S3, the cooling and solidification rate when smelting high-purity copper is 20-150K / min; the cooling and solidification rate when smelting high-purity nickel is 20-150K / min; the cooling and solidification rate when smelting high-purity copper-nickel alloy is 20-100K / min.
Citation Information
Patent Citations
Three-dimensional graphene reinforced copper-based composite material and preparation method and application thereof
CN117604491A
Preparation method of graphene-reinforced copper-based composite material with three-dimensional structure
CN110257795A
Preparation method for casting in-situ growth graphene reinforced copper composite material
CN113699405A
Process for preparing graphene
KR1020160134369A
Local carbon-supply device and method for preparing wafer-level graphene single crystal by local carbon supply
US20170130360A1
Cited By
Foaming cable copper conductor filled with carbon nanostructure and preparation method thereof
CN120913929A